PROTOTYPE ALAT TERAPI SHOULDER WHEEL DILENGKAPI MONITOR WAKTU TERAPI DAN SUDUT BERBASIS ARDUINO - Upik Ari Erlita; Bayu Setyo Wibowo; Muhammad Akbar Hariyono (Health Media, 2023)
Shoulder wheel is a therapeutic equipment used to train the movement of the joints in the shoulder and prevent muscle shrinkage. This tool utilizes the rotation of the motor to assist the patient in moving the arm so that the constriction of the blood vessels in this area will decrease and the shrinking of the muscles in the patient can be prevented and is expected to be able to move like normal conditions. This shoulder wheel therapy tool is made with additional angle and time monitors to make it easier for operators and patients to perform joint range of motion exercises optimally. The purpose of making this shoulder wheel therapy tool is to make it easier for physiotherapy users to examine patients so that further actions do not increase the risk of injury to the shoulder of patients who have frozen shoulder. The tool designed in this study is controlled by Arduino Uno by utilizing an optocoupler sensor as an angle sensor and a 16X2 LCD as a monitor for the duration of therapy. A DC motor is used to move the wheel so that the wheel can rotate so that it can help therapy for patients. Based on the results of measuring the power supply voltage, the average measured voltage value is 11.2 VDC. Then the Buzzer voltage measurement obtained an average value of 4.87 VDC and the optocoupler sensor measurement for an angle of 45 degrees had an error percentage of 3.8%, an angle of 90 degrees with an error of 0.58% and at an angle of 180 degrees with a percentage error value 1%.